2018
DOI: 10.1002/jcla.22634
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 allele frequencies, copy number variants, and tandems in the population of Hong Kong

Abstract: The present study provides a comprehensive analysis on the occurrences of CNV and tandems of the CYP2D6 gene in the Hong Kong population. The results contribute to the overall knowledge of pharmacogenomics and may accelerate the implementation of precision medicine in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The frequency of each actionable phenotype was derived from the allele frequency of the Hong Kong Chinese exome dataset based on the Hardy-Weinberg equation, except for CYP2D6 . The frequency of actionable phenotype of CYP2D6 was retrieved from a published Hong Kong study, since exome sequencing cannot detect haplotype and copy number variations accurately [ 27 ]. The projected prescription impact for each drug was estimated by multiplying the frequency of actionable phenotype by the total number of subjects for each individual drug retrieved from CDARS.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of each actionable phenotype was derived from the allele frequency of the Hong Kong Chinese exome dataset based on the Hardy-Weinberg equation, except for CYP2D6 . The frequency of actionable phenotype of CYP2D6 was retrieved from a published Hong Kong study, since exome sequencing cannot detect haplotype and copy number variations accurately [ 27 ]. The projected prescription impact for each drug was estimated by multiplying the frequency of actionable phenotype by the total number of subjects for each individual drug retrieved from CDARS.…”
Section: Methodsmentioning
confidence: 99%
“…While we report similar frequencies for CYP2D6 deletion or duplication alleles as in PharmGKB, we report a higher frequency than PharmGKB for the SV-containing haplotype *36 + *10 in East-Asians and another SV *68 + *4 in Europeans (Figure 5B, red annotated dots). Previously reported frequencies of *36 + *10 in East-Asians fall into a wide range (10-35%) 3237 , indicating the variability in CNV testing across assays. Additionally, *68 is often not interrogated in many studies, and it has been suggested that >20% of reported *4 alleles are actually in tandem with *68 38,39 .…”
Section: Resultsmentioning
confidence: 93%
“…Variation in CYP2D6 includes single-nucleotide variants (SNVs), indels, whole-gene deletions, multiplications, tandem arrangements and hybridisations [40,44]; it can also be affected by larger chromosomal deletions or other structural alterations as part of the rare 22q13 deletion syndrome, known as Phelan-McDermid syndrome. Currently, there are 133 CYP2D6 "star" ("*") alleles listed on the PharmVar data repository [45], as detailed within a recent and in-depth review of 2D6 nomenclature and 2D6 allele designation by Nofziger et al [46].…”
Section: An Overview Of Cyp2d6 Variationmentioning
confidence: 99%
“…The significance of this type of variation on the metaboliser phenotype of CYP2D6 depends on the functionality of the duplicated CYP2D6 allele. Indeed, it has been shown in a population of patients from Hong Kong that fewer than 20% of duplicated CYP2D6 alleles were duplications of functional alleles [44]. However, an increased copy number of functional CYP2D6 alleles increases the rate of metabolism of associated drugs [39], with some studies reporting as many as 13 copies of CYP2D6 in a single individual's genome [48].…”
Section: Copy Number Variationmentioning
confidence: 99%
See 1 more Smart Citation